Quantitative angiography methods for bifurcation lesions: a consensus statement update from the European Bifurcation Club - Collet, Carlos; Onuma, Yoshinobu; Cavalcante, Rafael; Grundeken, Maik; Généreux, Philippe; Popma, Jeffrey; Costa, Ricardo; Stankovic, Goran; Tu, Shengxian; Reiber, Johan; Aben, Jean-Paul; Lassen, Jens; et al. (EuroIntervention, 2017)
Bifurcation lesions represent one of the most challenging lesion subsets in interventional cardiology. The European Bifurcation Club (EBC) is an academic consortium whose goal has been to assess and recommend the appropriate strategies to manage bifurcation lesions. The quantitative coronary angiography (QCA) methods for the evaluation of bifurcation lesions have been subject to extensive research. Single-vessel QCA has been shown to be inaccurate for the assessment of bifurcation lesion dimensions. For this reason, dedicated bifurcation software has been developed and validated. These software packages apply the principles of fractal geometry to address the "step-down" in the bifurcation and to estimate vessel diameter accurately. This consensus update provides recommendations on the QCA analysis and reporting of bifurcation lesions based on the most recent scientific evidence from in vitro and in vivo studies and delineates future advances in the field of QCA dedicated bifurcation analysis.